Freight transport development forecasts in enterprises management - M. Kadłubek (Global Journal of Environmental Science and Management)
In this study, an investigation of long-term forecasts relating to the development of the transport sector in Poland is performed, including the ones by 2030 and 2050. Selected transport development forecasts from the perspective of the membership of Poland in the European Union are presented and most of all, from the perspective of national studies. The basement for the review was the prognosis of European Commission, Central Statistical Office, International Monetary Fund, Department of Economic, Sectoral and Agricultural Market of BGZ BNP PARIBAS S.A., Motor Transport Institute, Wise Europa Institute of Warsaw Transport Institute, as well as prognosis of the scientific experts. Despite temporary economic downturns, the demand for freight transport is steadily growing and, as shown by the forecasts, it will grow in the future. In 2018 the situation on the freight transport market was expected to remain stable, mainly due to the continuous high demand for international carriages.